STRATEGI PEMBERDAYAAN DALAM MENGOPTIMALKAN POTENSI AGRIBISNIS DI PEDESAAN KABUPATEN HALMAHERA BARAT PROPINSI MALUKU UTARA - Haris Mahmud; Mila Fatmawati; Mardiyani Sidayat; Nurdiyanawati Djumadil; Natal Basuki; Fatmawati Kaddas (Jurnal Abdimas Bina Bangsa, 2024)
The realization of agribusiness actors is carried out through rolling agricultural strengthening facilities in the context of strengthening group institutional finances, increasing entrepreneurship and fostering productive economic businesses. The agribusiness community empowerment program through business strengthening groups is a follow-up to previous empowerment programs. In this way, it is hoped that there will be no more confusion in the interpretation of this empowerment program with direct community assistance. It is hoped that this kind of empowerment pattern can stimulate the growth of agribusiness business groups and accelerate the formation of agribusiness institutional networks in the West Halmahera region. So that agricultural development programs can be achieved and implemented carefully. The results of the service show that the strategy for empowering the agribusiness community in optimizing agribusiness potential is by using 4 strategies, namely: 1) providing support for empowering the agribusiness community in the form of procuring agricultural production facilities; 2) strive to create regional regulations that can support the empowerment of agribusiness communities; 3) empowering the agribusiness community as a whole through active participation from the local government; and 4) provide coaching or guidance to each individual/farmer group on how to properly empower the agribusiness community